Frequency of Oral Squamous Cell Carcinoma of Tongue in patients presenting to Ayub Teaching Hospital Abbottabad - Akram, Umair; Hilal, Rashida; Hassan, Raheel; Bukhari, Abid (Pakistan Journal of Medical & Health Sciences, 2024)
Aim : To determine the frequency of oral squamous cell carcinoma of tongue in patients presenting at Ayub Teaching Hospital Abbottabad. Study Design: Cross- Sectional (Descriptive) Study. Place and duration of study: Department of Dentistry, MTI-ATH Abbottabad from 24th December 2020 to 25th June 2021. Methodology: One hundred and sixty-six patients of oral squamous cell carcinoma of oral cavity were enrolled. Patients of age 20-80 years of age, both genders, confirmed after histopathological examination (biopsies) were included. Patients not confirmed by biopsy and squamous cell carcinoma of other intra oral sites were excluded. Results: There were 126(75.9%) males and 40(24.1%) females with mean age 56.61±9.50 years and mean duration of disease 3.64±1.56 years. 22(13.3%) patients had oral squamous cell carcinoma of tongue. Practical implication: The benefit of the present study is highlighting the alarming increasing incidence of oral tongue squamous cell carcinoma during the last decades, specifically in women and younger patients without the traditional risk factors of alcohol or tobacco use. Conclusion: Oral squamous cell carcinoma is prevalent among males and people of higher age group with only 13.3% having tongue as primary site.